Volume or value? How relative performance information affects task strategy and performance - Philipp Schreck (Journal of Business Economics, 2020)
Employees face volume–value trade-offs when they perform tasks with multiple characteristics, leaving them with a choice between different strategies towards the goal of maximizing the total value of their output. Either they produce many, less valuable units of output (volume strategy); or fewer, more valuable units (value strategy). In such a situation, the provision of relative performance information (RPI) may be useful for both, motivating employees to exert high levels of effort, and helping them to find the optimal strategy relative to their individual abilities. The study investigates how useful two common forms of RPI—simple and detailed—are in improving the performance of employees who face volume–value trade-offs. In particular, it analyzes how group composition in terms of the group members' relative abilities moderates the behavioral consequences of RPI. Results of a laboratory experiment suggest that the behavioral effects of RPI depend on group composition, indeed: While in homogeneous groups, performance is highest under simple RPI, in heterogeneous groups, performance is highest under detailed RPI.
Keywords: M12; M41; M54; 650; Incentives; Motivation; Rankings; Relative performance information; Task strategy